2021
DOI: 10.2147/idr.s336418
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Survey of Antimicrobial-Resistance Bacteria in the Sewage Tank Replacement with Hospital Relocation

Abstract: Background: Excrement containing antimicrobial-resistant bacteria (ARB) is discharged from the hospital sewage through wastewater treatment plants (WWTP) into rivers, increasing the antimicrobial resistance (AMR) burden on the environment. Purpose: We illustrate the contamination of hospital sewage tanks with ARB harboring antimicrobial resistance genes (ARGs) using comprehensive metagenomic sequencing. During the study period, we moved to a new hospital building constructed for renovation. Therefore, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Recent research provides insights into the environmental risk assessment of both AMRB and AMRGs [ 8 , 35 , 112 ]. The risk of infection by AMRB in water and via the ecosystem is increasing, and further development of AMRB in the presence of residual antimicrobials or AMRGs in water is now progressing [ 12 , 113 , 114 , 115 ]. Further, the present study might provide invaluable information to prevent infectious diseases from the aquatic environment, including wastewater.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research provides insights into the environmental risk assessment of both AMRB and AMRGs [ 8 , 35 , 112 ]. The risk of infection by AMRB in water and via the ecosystem is increasing, and further development of AMRB in the presence of residual antimicrobials or AMRGs in water is now progressing [ 12 , 113 , 114 , 115 ]. Further, the present study might provide invaluable information to prevent infectious diseases from the aquatic environment, including wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…The spread of AMRB not only makes it difficult to treat infectious diseases but also increases the risk of epidemics and aggravation. Taking effective measures to prevent the prevalence of AMRB has become urgent [ 10 , 11 , 12 ]. The connection between humans and the environment continues to complicate.…”
Section: Introductionmentioning
confidence: 99%
“…Recently there have been studies combining both metagenomic and culture-based analyses [ 25 , 46 , 47 ] but none of these have correlated resistance/susceptibility phenotypes in cultured isolates with metagenomic data. Two recent studies used metagenomic samples to predict AMR and virulence determinants (by comparison of known genes in public databases) of clinical infections; however, typically these samples were mono-or polymicrobial with at most two species [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the synergy between plasmids and ARGs with flanking insertion sequences (ISs) has also been documented to potentiate the emergence of MDR-hypervirulent clones between WWTP- and human/animal-associated bacteria [ 5 ]. Ekanzala et al reported that hospital wastewater showed significantly higher environmental resistome risk scores than all other assessed matrices [ 9 , 10 ], suggesting that hospital wastewater, effluent, and sewage sludge should be subjected to stringent mitigation measures to minimize such dissemination. Therefore, urban WWTPs are among the main sources of ARB and ARGs released into the environment [ 11 ].…”
Section: Introductionmentioning
confidence: 99%